Genetic Characteristics Of White Shrimp (Litopenaeus Vannamei) In Banyuwangi And Situbondo: The Infected White Spot Syndrome Virus (WSSV) - kilawati, yuni; Maimunah, Yunita (Journal of Food and Life Sciences, 2018)
Water pollution caused by human anthropogenic activities has deteriorating effect on water quality for aquaculture. Therefore, the objectives of this research were to determine how water quality, population and shrimp genetic characteristic in polluted area. Especially in East Java which have high virulency on WSSV outbreaks.Data exploration using surveillance technique was collecting physical and chemical water quality parameters. Shrimp samples were analyzed for morphological and genetical characteristics using specific WSSV primer ICP 11.Water quality at all sampling locations were categorized as polluted refers to ammonia and TOMÂ  concentrations. Low water quality acts as a trigger for WSSV outbreaks. Shrimp pond from Situbondo exhibited as carrier indicated by the presence of WSS infection based on genetic characteristics, while morphological characteristics did not.